PENGARUH MOTIVASI MENGHINDARI RIBA DAN PENGETAHUAN PRODUK PERBANKAN SYARIAH TERHADAP KEPUTUSAN MENJADI NASABAH DI BANK JABAR BANTEN SYARIAH KCP CIAMIS - Eka Fitria; Sumadi Sumadi; Eggy Armand Ramdani (Syari'ah Economics, 2019)
This study aims (1) to determine the effect of the motivation to avoid usury on the decision to become a customer at Bank Jabar Banten Syariah KCP Ciamis; (2) to determine the effect of product knowledge on the decision to become a customer at Bank Jabar Banten Syariah KCP Ciamis; and (3) to determine the effect of motivation to avoid usury and knowledge of Islamic banking products on the decision to become a customer at Bank Jabar Banten Syariah KCP Ciamis. This quantitative research uses the correlational method. The results showed that (1) there was an influence of the motivational variable to avoid usury on the decision to become a customer at BJBS KCP Ciamis. This is evidenced by the value of t-count (2.058) > t-table (2.051); (2) there is an influence of knowledge of Islamic banking products on the decision to become a customer at BJBS KCP Ciamis. This is evidenced by t-count (2,920) > t-table (2,051); and (3) simultaneously, the variables of motivation to avoid usury and knowledge of Islamic banking products together influence the decision to become a customer at BJBS KCP Ciamis. This is shown from f-count (27.534) > f-table (3.354).